Reflected wave intensity increases based on aortic diameter after endovascular aortic therapy in a goat model - Takano, Tomohiro; Iwai-Takano, Masumi; Tsuboko, Yusuke; Shiraishi, Yasuyuki; Yambe, Tomoyuki; Igarashi, Takashi; Yokoyama, Hitoshi (Scientific reports, 2021)
Reflected wave increases after endovascular aortic repair (EVAR) in patients with aortic aneurysm. This affects the left ventricular (LV) diastolic function and leads to a poor prognosis. This study aimed to evaluate the relationship between increased reflected wave amplitude and aortic diameter after EVAR. EVAR was performed in seven healthy goats. We assessed wave intensity (WI), aortic diameter, and stiffness parameter β. Moreover, we evaluated the relationship between negative reflected wave (NW, reflected waves toward the heart from the periphery by WI) and other parameters after EVAR. Results showed an increase in stiffness parameter β (3.5 ± 0.3 vs 15.9 ± 4.7, p = 0.018) and a decrease in the change of aortic diameter (6.9 ± 0.7 vs 2.7 ± 0.4%, p = 0.018) after EVAR. The NW was significantly amplified after EVAR from baseline (−589.8 ± 143.4 to  − 1192.3 ± 303.7 mmHg-m/sec 3 , p = 0.043). The NW showed a significant correlation with maximum aortic diameter (R = 0.707, p = 0.038) and minimum aortic diameter (R = 0.724, p = 0.033). The reflected wave was enhanced after EVAR and was correlated to the aortic diameter at the stent-graft site. It is important to consider that patients with smaller aortic diameters in landing zone who undergo EVAR may develop LV dysfunction.